Condylar position and morphology in bilateral partially edentulous patients: a radiographic perspective - Asymal, Alhidayati; Nurrachman, Aga Satria; Astuti, Eha Renwi; Mulyani, Sri Wigati Mardi; Ramadhani, Nastiti Faradilla; Savitri, Yunita; Zulkarnain Putri, Adinda Melanita; Izza, Raden Lailatul (Jurnal Radiologi Dentomaksilofasial Indonesia (JRDI), 2025)
Objectives:Tooth loss is a common oral health issue in the general population, with its prevalence increasing significantly with age. Tooth loss that is not immediately rehabilitated with dentures can lead to disruption of the occlusion pattern. This condition may be influenced by the position of the condyle and can also result in morphological alterations of the mandibular condyle. If left untreated for an extended period, these changes may significantly impact the temporomandibular joint (TMJ). Materials and Methods:The sample used in this study consisted of secondary data obtained from panoramic radiographs of bilaterally partially edentulous patients with high-quality radiographic standards. Results:The findings of this study demonstrate alterations in mandibular condyle position, with 57.7% of cases showing an anterior position and 13.7% showing a retroposition in patients with bilateral partial edentulism. The most dominant condylar morphology observed was the pointed shape (36.3%), whereas the least common was the flat shape (5.7%). Conclusion:The results of this study indicate that the anterior position and pointed shape were the most common condylar position and morphology. This distribution was found to be higher in women than in men, with hormonal, anatomical, and habitual factors influencing the distribution of pressure on the temporomandibular joint (TMJ).